198. Infective Endocarditis Among Solid Organ Transplant Recipients in the United States - Eichenberger, Emily (Open Forum Infect Dis, 2020)
BACKGROUND: With over 30,000 solid organ transplants (SOT) performed annually the United States alone, there is an urgent need to understand the risks and outcomes of infective endocarditis (IE) in SOT recipients. METHODS: We used data from the 2013–2017 Nationwide Readmissions Database (NRD). Hospitalizations associated with IE were identified using diagnosis and procedure codes. The cohort included all patients with IE, stratified by history of solid organ transplant (heart, liver, kidney, lung, intestines, pancreas). Outcomes included 60-day rates of mortality, (extracorporeal membrane oxygenation) ECMO deployment, thromboembolic events, length of stay, and inpatient costs. Regression models, weighted to account for the NRD sample design, were used to model associations between outcomes and transplant history, adjusting for patient age, sex, facility characteristics, comorbid conditions, and potential IE organism. RESULTS: A total of 175,682 hospitalizations associated with IE, corresponding to a national estimate of 345,236, were included. Of these, 1,299 (weighted estimate = 2,511) were associated with history of transplant. Transplant recipients were younger (54.2 vs. 59.4 years, p < 0.001), less likely to be female (33.2% vs. 40.1%), had higher rates of renal and liver disease (93.1% vs. 39.2% and 16.2% vs. 8.6%, respectively, p < 0.001 for both). The most common SOT organ (allowing for multiple organs) was kidney (75%) followed by liver (11.5%) and heart (10.5%). Compared to non-SOT patients with IE, SOT recipients with IE were associated with lower risk of mortality [adjusted relative risk (aRR): 0.74, 95% confidence interval (CI) (0.61, 0.89)], lower risk of prolonged mechanical ventilation [aRR 0.80 (0.68, 0.93)], 2.2 fewer inpatient days (-3.5 to -0.8) and $7,000 lower charges (-$9,700, -$4,300), after adjustment. [Image: see text] CONCLUSION: IE complicated by SOT history was associated with paradoxically better outcomes than IE in patients without SOT history. The selection process underlying receipt of transplant may partially explain these differences in outcomes. DISCLOSURES: Vance G. Fowler, Jr., MD, MHS, Achaogen (Consultant)Actavis (Grant/Research Support)Advanced Liquid Logics (Grant/Research Support)Affinergy (Consultant, Research Grant or Support)Affinium (Consultant)Allergan (Grant/Research Support)Ampliphi Biosciences (Consultant)Basilea (Consultant, Research Grant or Support)Bayer (Consultant)C3J (Consultant)Cerexa (Consultant, Research Grant or Support)Contrafect (Consultant, Research Grant or Support)Cubist (Grant/Research Support)Debiopharm (Consultant)Destiny (Consultant)Durata (Consultant)Forest (Grant/Research Support)Genentech (Consultant, Research Grant or Support)Integrated Biotherapeutics (Consultant)Janssen (Consultant, Research Grant or Support)Karius (Grant/Research Support)Locus (Grant/Research Support)Medical Biosurfaces (Grant/Research Support)Medicines Co. (Consultant)Medimmune (Consultant, Research Grant or Support)Merck (Consultant, Research Grant or Support)NIH (Grant/Research Support)Novadigm (Consultant)Novartis (Consultant, Research Grant or Support)Pfizer (Grant/Research Support)Regeneron (Consultant, Research Grant or Support)Tetraphase (Consultant)Theravance (Consultant, Research Grant or Support)Trius (Consultant)xBiotech (Consultant)